Effective pack practices to control postharvest diseases in small berries - McDaniel, Austin (Kansas State University, 2019)
Postharvest losses can occur anywhere from harvesting to handling and shipping. In 2014, approximately $30 billion of fresh produce were lost in the United States food supply chain. In particular, small fruits shelf-life can be reduced by weight loss, stem scar injury, gray mold and ripe rot. It is important therefore to find sustainable packing alternatives to protect produce, increase shelf-life, minimize waste, and preserve resources. The objectives of this study were to: 1) evaluate the mechanical, physical and anti-fungal properties of pullulan packaging films loaded with essential oil (EO) nanoemulsions; 2) investigate the effectiveness of the formulated active packaging systems to extend shelf-life and enhance strawberries’ quality. Food-grade emulsions with sub-micron droplets were used to encapsulate cinnamaldehyde (CIN), eugenol (EUG) and thymol (THY) within either a refined coconut oil (carrier) or palm stearin in pullulan packaging systems. Different film combinations loaded with EO nanoemulsions were studied. Tensile strength, moisture content and antifungal activity against Rhizopus stolonifer, Alternaria spp., and Aspergillus niger were measured and compared to control pullulan systems. A lower tensile strength (P > 0.05) was measured for combinations loaded with EO nanoemulsions as compared to films without active lipid solutions. Nevertheless, the active combinations presented good elasticity and ductility. The control formulations showed no antifungal activity. Conversely, active combinations exhibited significant inhibition zones against postharvest fungi (P < 0.05). Film containing CIN had the biggest inhibition halos: 13.7, 15.7 and 14.5 mm were measured against R. stolonifer, Alternaria and A. niger, respectively. Pullulan films incorporated with CIN nanoemulsions were selected for the field study. Fresh strawberries were harvested from a local farm in Kansas and separated into two groups (control and treatment). For each group, 10 strawberries were placed into a molded fiber berry basket. A pullulan film was added at the bottom of each container for the treated group. Samples were stored for up to 10 days at 3°C and 12°C. Every 2 days microbial, visual, and physiological quality parameters were evaluated. For treated strawberries stored at 3°C, a reduction of 2 log CFU/g in yeast and mold population was observed over the 10-day period (P <0.05), as compared to the control. An improvement in visual quality was noted for treated berries at both storage temperatures as compared to the control group. Overall, a reduction of fungal and quality decay in strawberries packaged with pullulan films incorporated with nanoemulsions was observed. This study demonstrates the potential application of pullulan active packaging systems as a mean of controlling and reducing postharvest disease in small fruits during shipping and storage.
Keywords: Postharvest; Active Packaging; Essential Oils; Pullulan